NETWORK PHARMACOLOGY-GUIDED TARGET IDENTIFICATION OF CADAMBINE AND DERIVATIVES FROM NEOLAMARCKIA CADAMBA AGAINST ALZHEIMER’S DISEASE WITH IN SILICO ADMET PROFILING - KAVITHA M; RONALD DARWIN C (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: To identify Alzheimer’s disease (AD)-relevant molecular targets of cadambine and its derivatives from Neolamarckia cadamba using a predictive network pharmacology framework and to evaluate their drug-likeness, permeability, and safety through in silico ADMET profiling. Methods: Disease genes were obtained from GeneCards, whereas compound targets for cadambine, 3-dihydrocadambine, and 3β-isodihydrocadambine were predicted through SwissTargetPrediction. Overlapping targets were analyzed using STRING and Cytoscape for protein–protein interactions and node centrality. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment provided functional insights. SwissADME and ProTox 3.0 assessed physiochemical, permeability, and toxicity profiles. In recent years, network pharmacology has matured into a robust, systems-level methodology that integrates polypharmacology, systems biology, bioinformatics, and network modeling to elucidate complex disease mechanisms and multitarget drug actions. Contemporary studies published in 2024–2025 demonstrate the application of network pharmacology to AD contexts, combining target prediction with gene-disease association data and pathway enrichment to reveal multi-pathway therapeutic hypotheses and actionable biological insights. Results: Key hub targets included caspase-3, epidermal growth factor receptor, peroxisome proliferator-activated receptor gamma, matrix metalloproteinase-9/matrix metalloproteinase-2, solute carrier family 2 member 1, and adenosine receptors, linked to apoptosis, neuroinflammation, and metabolism. GO/KEGG analysis revealed neuronal membrane localization and G protein-coupled receptor signaling. ADMET predicted low blood– brain barrier permeability, low acute toxicity (LD₅₀ 3000 mg/kg), and possible immuno- and respiratory toxicity. In vitro assays demonstrated dose-dependent enhancement of antioxidant enzyme activities, supporting a general neuroprotective phenotype. Conclusion: Cadambine and its derivatives exhibit multitarget potential relevant to AD through network-level modulation of oxidative stress, inflammatory, and signaling pathways. These findings support further target-specific validation and formulation-based strategies to improve central nervous system delivery.